2018
DOI: 10.1111/jar.12468
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quadriceps strength in adults with severe or moderate intellectual and visual disabilities: Feasibility and reliability

Abstract: The MSST, the LE, and the 30sCS are feasible tests for measuring muscle strength in persons with SIVD, having sufficient test re-test reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…2007) and has been used in studies of adults with ID (Dijkhuizen et al . 2018). Individuals with motor function level 1 may have limitations in advanced motor skills; level 2 usually require stair railings, walk unassisted, but may occasionally use assist devices; level 3 require walking assist devices inside and usually outside and levels 4 and 5 usually require a wheelchair for mobility.…”
Section: Methodsmentioning
confidence: 99%
“…2007) and has been used in studies of adults with ID (Dijkhuizen et al . 2018). Individuals with motor function level 1 may have limitations in advanced motor skills; level 2 usually require stair railings, walk unassisted, but may occasionally use assist devices; level 3 require walking assist devices inside and usually outside and levels 4 and 5 usually require a wheelchair for mobility.…”
Section: Methodsmentioning
confidence: 99%
“…If a learning period was required to perform the leg extension test in an appropriate/reliable way, the 1RM was measured later in the first week of the PRT programme. The leg extension test has shown to be a feasible and reliable instrument for measuring Quadriceps strength in persons with moderate and severe ID with visual impairment (Dijkhuizen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In past research, persons with (severe) ID and visual impairment required a learning period of four to five times for adequately performing the leg extension test in an appropriate/reliable manner (Dijkhuizen et al, ). In this study, we determined whether a participant could properly perform the leg extension test in Week 1, that is, by performing the 1RM up to the maximum without any compensation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that clinical tests of balance and gait are feasible in adults with mild to moderate intellectual disabilities (Enkelaar et al, 2013). Sufficient feasibility and test-retest reliability in lower extremity strength tests in 29 adults with severe or moderate intellectual and visual disabilities has been reported, but behaviour or communication problems may influence the examination results (Dijkhuizen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%